Inovasi Strategi Pemasaran Pembiayaan Mas Antam Pada Produk Arrum Haji ( Studi PT Pegadaian Syari’ah Bangil – Pasuruan ): Inovasi Strategi Pemasaran Pembiayaan Mas Antam Pada Produk Arrum Haji ( Studi PT Pegadaian Syari’ah Bangil – Pasuruan ) - Azizah, Lailatul (Airlangga Journal of Innovation Management, 2024)
The fact is that every year the departure quota for prospective hajj pilgrims is relatively small and the waiting list is quite long, draining time, money & energy. With the high level of community need for hajj financing, Shari'a Leasing Company Bangil–Pasuruan is here. As a business opportunity/enterprise that operates in the field of hajj financing products (hajj arrum), an easy, fast, precise, and safe solution in overcoming the problem of registration needs & obtaining a hajj portion number, especially in middle to lower economic communities, just by pawning gold from antam as collateral with the financing concept: no banks, usury, fines and confiscations. Through the application of the concept of rahn, ijarah & qard contracts. From the results of field data analysis, it is clear that there are 4 forms of innovation in gold from antam financing strategy applied to arrum hajj products, name: 1. product (gold savings program with 4T concept on credit), 2. price (gold from antam guarantee 3.5 grams customers can make & get a hajj portion number, and freely choose the number of installments & period according to economic conditions. 3. promotion (product introduction carried out online & offline), 4. service (friendly, policy, practical, easy, fast and safe). To be able to anticipate business risks for customers who fail to pay pawnshops should be able to select/measure credit worthiness by applying the 5C principles.